(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Heidegger Being and Time’s notions of anxiety, authenticity and existentiell modification can be understood as a process of self-knowledge and personal change. It is argued that Heidegger himself exemplifies that process, a relevant one to the practice of psychotherapy.